2021
DOI: 10.1186/s12879-021-06412-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of human adenoviruses among hospitalized patients with respiratory tract infections in a tertiary Hospital in Guangzhou, China between 2017 and 2019

Abstract: Background Human Adenoviruses (HAdVs) cause a wide array of illnesses in all age groups. They particularly cause frequent morbidity among children. In China, human adenovirus types 3, 4, 7, 11, 14, 21, and 55 have caused at least seven outbreaks since 2000. However, limited studies are available regarding the epidemiological patterns and diversity of HAdVs types among hospitalized patients with respiratory tract infections (RTIs). Methods To unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…We did not observe any gender difference in HAdV infection, which is consistent with previous studies conducted in other provinces and countries [16,17]. The highest HAdV positive proportions were observed among children over six years of age, which was similar to some other studies done in Guangzhou [16,18]. A study on seroprevalence and titer levels of neutralizing antibodies (NAb) against HAdV in healthy populations in 2017 from Guangzhou showed that the HAdV antibodies in children over five years were higher than those in other age groups, which was consistent with the results of the present study [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not observe any gender difference in HAdV infection, which is consistent with previous studies conducted in other provinces and countries [16,17]. The highest HAdV positive proportions were observed among children over six years of age, which was similar to some other studies done in Guangzhou [16,18]. A study on seroprevalence and titer levels of neutralizing antibodies (NAb) against HAdV in healthy populations in 2017 from Guangzhou showed that the HAdV antibodies in children over five years were higher than those in other age groups, which was consistent with the results of the present study [19].…”
Section: Discussionsupporting
confidence: 92%
“…Sequence variation analysis indicated that three genes (penton base, hexon, and fiber) of HAdV-7 were relatively stable across time and geographic space, particularly for viruses within sub-types, which shared almost the same variation sites [27]. Molecular typing of human adenoviruses among hospitalized patients with RTI (respiratory tract infection) in Guangzhou between 2017 and 2019 indicates stable conservation of HAdV-3 and -7 [18]. Other research showed the nucleotide sequence homologies of the hexon, fiber and penton gene for HAdV-7 and HAdV-3 in Guangzhou between 2013 and 2019 were high (99.5-100%) [16], suggesting low strain variation among the circulating viruses.…”
Section: Discussionmentioning
confidence: 98%
“…Adenovirus infection spread is usually dependant on age of an individual, geographic and seasonal difference dynamics and other demographic factors that affect disease occurrence such as close living conditions and the immune status of an individual [10,18]. Studies have reported a high prevalence of up to 49.6% in a military population in Korea [19], 2.0-6.1% in hospitalized patients in Guangzhou City, China [20] and among organ transplant patients, 64% were reported to have developed adenovirus disease [21].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 HAdVs are classified into seven different species (A-G) according to genomics, serology, and biological characteristics, and consist of at least 103 types to date. 3,4 Different HAdV types can cause a wide range of clinical symptoms, including upper and lower respiratory tract infection, pneumonia, conjunctivitis, gastroenteritis, acute hemorrhagic cystitis, nephritis, and neurological diseases. 5,6 HAdV-55 is a reemergent pathogen in recent years, which was originally described as HAdV-11a in an outbreak of ARD that occurred in Qishan, Shanxi Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Human adenoviruses (HAdVs) are usually associated with acute respiratory diseases (ARDs) worldwide, which are responsible for 1%–7% of ARD and for 4%–10% of childhood pneumonia throughout the world 1,2 . HAdVs are classified into seven different species (A–G) according to genomics, serology, and biological characteristics, and consist of at least 103 types to date 3,4 . Different HAdV types can cause a wide range of clinical symptoms, including upper and lower respiratory tract infection, pneumonia, conjunctivitis, gastroenteritis, acute hemorrhagic cystitis, nephritis, and neurological diseases 5,6 .…”
Section: Introductionmentioning
confidence: 99%